2017
DOI: 10.18632/oncotarget.22675
|View full text |Cite
|
Sign up to set email alerts
|

Association between SOD1, CAT, GSHPX1 polymorphisms and the risk of inflammatory bowel disease in the Polish population

Abstract: PurposeThe main aim of this study was investigate the association between the genetic polymorphism of antioxidant enzyme genes: SOD1, CAT and GSHPX1 and the risk of inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis in the Polish population.MethodsA total of 445 subjects including 200 patients with IBD and 245 controls were allowed in this study. We determined activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx1) and examination their association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…In the literature, there are reports about the role of SOD isoenzymes as therapeutic factors in inflammation [ 5 , 6 , 7 , 10 ]. It has been shown that there is an association between the single-nucleotide polymorphism (SNP) in the genes of SOD isoenzymes (especially SNP rs2070424 in the SOD1 gene) and inflammation and Cu concentration as a regulator of their activity [ 15 , 16 ]. However, the levels of individual SOD isoenzymes in patients with acute pancreatitis (AP) have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are reports about the role of SOD isoenzymes as therapeutic factors in inflammation [ 5 , 6 , 7 , 10 ]. It has been shown that there is an association between the single-nucleotide polymorphism (SNP) in the genes of SOD isoenzymes (especially SNP rs2070424 in the SOD1 gene) and inflammation and Cu concentration as a regulator of their activity [ 15 , 16 ]. However, the levels of individual SOD isoenzymes in patients with acute pancreatitis (AP) have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…No CAT gene polymorphism was seen in 200 patients of enteropathic arthritis or patients of inflammatory bowel disease (IBD )in Poland 24 . A study conducted in Iran concluded that CT genotype of CATC262T polymorphism increased the risk of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we found a significant difference in 4 out of the 14 CAT-gene SNPs evaluated (rs7943316, rs475043, rs769217, and rs525938) between the CD patients and the control group (Table 3). Some of these four polymorphisms have been previously implicated with the pathogenesis of inflammatory bowel disease (IBD) [16,18,19].…”
Section: Snps In the Catalase Gene Are Associated With The Risk Of Cr...mentioning
confidence: 99%